TO STUDY THE EFFECT OF GUGGUL, LAKSHA AND ARJUN CHURNA IN THE MANAGEMENT OF KANDA BHAGNA (International Journal of Ayurveda and Pharma Research, 2016)
Ayurvedic texts have illustrated fracture as being the loss in the continuity of the bone due to pressure. The management of long bone fracture runs through the basic principle of fracture management e.g. -Reduction, Immobilisation and Rehabilitation. In ancient treatise so many indigenous compounds are mentioned which can promote the healing of fracture. With reference to Vangasen, an indigenous compound named as Guggul, Laksha and Arjun Churna is also praised for Bhagna sandhaana. Taking this reference into consideration Arjun Guggul and Laksha churna was taken for the study. Fracture management was according to the basic principle of management of fracture i.e pop casting was done. The Churna of Arjun, Guggul and Laksha were made according to the method given in Bhaisajya Ratnavali. In all 30 patients were treated in which 15 patients were treated with Arjun, Guggul and Laksha churna and was given with milk. Rest 15 patients were treated with the calcium supplement. Follow-up was taken on 0, 15th, 30thand 45th day. During this study it was observed that on zero days there was tenderness as well as pain present but there was no bluish discolouration and also movements of digits were there. On 15th day there was mild pain and tenderness. But swelling was not present as well as callus formation was not there. In this study it was observed that callus formation was late in first group as well as pain tenderness and swelling was decreased early. In the 2nd group pain, tenderness and swelling was decreased and also callus formation was seen early compared to 1st group.